2010
DOI: 10.1016/j.snb.2009.11.067
|View full text |Cite
|
Sign up to set email alerts
|

Palladium/silicon nanowire Schottky barrier-based hydrogen sensors

Abstract: a b s t r a c tThis work presents the design, fabrication, and characterization of a hydrogen sensor based on a palladium/nanowire Schottky barrier field-effect transistor that operates at room temperature. The fabricated sensor consists of boron-doped silicon nanowire arrays that are contact printed on top of a SiO 2 /Si substrate with subsequently evaporated Pd contacts. The fabrication process is compatible with post-CMOS and plastic substrate integration as it can be completed at temperatures below 150• C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 133 publications
(82 citation statements)
references
References 31 publications
2
72
0
6
Order By: Relevance
“…For example, p-type Si-nanowire arrays were configured as H 2 sensors. 173 To enhance sensitivity to H 2 , a 2 nm-thick Pd film was deposited on the printed nanowire array, resulting in the formation of Pd nanoclusters on the nanowire surfaces. It is found that the conductance of the Si-nanowire array shows a strong dependence on the H 2 exposure, even at relatively low concentrations (250 ppm).…”
Section: Sensors and Detectorsmentioning
confidence: 99%
“…For example, p-type Si-nanowire arrays were configured as H 2 sensors. 173 To enhance sensitivity to H 2 , a 2 nm-thick Pd film was deposited on the printed nanowire array, resulting in the formation of Pd nanoclusters on the nanowire surfaces. It is found that the conductance of the Si-nanowire array shows a strong dependence on the H 2 exposure, even at relatively low concentrations (250 ppm).…”
Section: Sensors and Detectorsmentioning
confidence: 99%
“…Traditionally, the high work function metal palladium (Pd) has been used as the most popular contact material to the valence band of various nanostructures, including nanotubes, graphene, and organics [7] [8] [9] [10]. However Pd alone has proven insufficient as a hole contact for TMDC devices.…”
mentioning
confidence: 99%
“…Pd particles are mainly used as H 2 sensing materials and form PdH x upon exposure to H 2 gas molecules through dissociative adsorption, resulting in changes in the resistance of the substrate. 28 It is extensively used as a catalyst metal for the enhancement of H 2 S gas adsorption over a wide range of temperatures and enables detection even at room temperature. 29,30 Hydrogen sulde gas also shows dissociative adsorption at the surface of the catalytic Pd clusters, then diffuses before interacting with other reacting adsorbate oxygen species in atmospheric conditions.…”
Section: -11mentioning
confidence: 99%